The Effect of Five Bottom Line, Business Ethics, and Leadership on SDGs Desa With GCG as a Moderating Variable (Case Study on BUM Desa Kabupaten Bogor) - Mulyaningsih, May; Sudibyo, Yvonne Augustine (Technium Social Sciences Journal, 2022)
This descriptive exploratory research aims to determine the extent of the implementation of the SDGs Desa in the Village through the role of BUM Desa. The population of the study was 416 BUM Desa in Kabupaten Bogor. The sampling method is accidental sampling by distributing printed questionnaires, therefore the research sample was 141 BUM Desa who filled out and returned the research questionnaire. The research objects are the five bottom line, business ethics, and leadership as independent variables, while the SDGs Desa as the dependent variable, and GCG as the moderating variable. The unit of analysis is the organization, the research location is BUM Desa in Kabupaten Bogor with the research period from November to December 2021. The research method uses a mixed method. Sources of primary data through questionnaires and interviews, while secondary data through literature studies. The type of data used is quantitative data in the form of closed-ended questionnaires using a Likert scale which was statistically tested using SPSS and qualitative data in the form of interviews with Chief of Forum BUMDes Kabupaten Bogor.